Euthanasia: looking from the perspectives of common law, civil law and Islamic law / Jacques Jimmy Yangus … [et al.] - Yangus, Jacques Jimmy; Hashim, Najmin Shahnaz; Chula @ Nicholas, Navaron; Mohamad Idrakisyah, Mohamad Azfarsyah (2014)
This dissertation aims to examine the current legal position of euthanasia from the perspectives of civil law, common law and Islamic law. Throughout this study, four issues in the euthanasia debate are examined, which are active euthanasia, the administration of double effect medication, passive euthanasia, and the enforceability of advance directives. Both active and passive euthanasia are chosen for this study because they are the main principal and important issues within the euthanasia debate. Besides, advance directives are equally important issues to be discussed because it is the extension of both active and passive euthanasia whereby patients are given the rights to choose for the future treatment as they wish. In addition, the study of double effect medication is included to determine whether it might be used as concealment by physicians to practice euthanasia. The examination of these four important issues in euthanasia includes an examination of the current law in common and civil law countries as well as countries practicing Islamic law. Furthermore, interviews were conducted with physicians in Malaysia to obtain their experience and perceptions on the issue of euthanasia to provide useful practice insights of euthanasia.